2018
DOI: 10.1098/rsif.2018.0494
|View full text |Cite
|
Sign up to set email alerts
|

Posner qubits: spin dynamics of entangled Ca 9 (PO 4 ) 6 molecules and their role in neural processing

Abstract: It has been suggested that 31 P nuclear spins in Ca 9 (PO 4 ) 6 molecules could form the basis of a quantum mechanism for neural processing in the brain. A fundamental requirement of this proposal is that spins in different Ca 9 (PO 4 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(53 citation statements)
references
References 37 publications
(80 reference statements)
5
43
2
Order By: Relevance
“…The hypothesis is this: that phosphorus nuclear spin might function as a neural qubit to allow for quantum processing to play a role in cognition [84][85][86] 198,201 . However, they argue that these extended times are partly due to experimental control of the coherent spin dynamics, a condition that Fisher does not take into account 198 . In their analysis of Posner spin dynamics they take a number of other factors into account such as dipolar and scalar couplings within Posner molecules as well as the Zeeman interaction of the phosphorus spins with the geomagnetic field 198 .…”
Section: Entangled Posner Moleculesmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis is this: that phosphorus nuclear spin might function as a neural qubit to allow for quantum processing to play a role in cognition [84][85][86] 198,201 . However, they argue that these extended times are partly due to experimental control of the coherent spin dynamics, a condition that Fisher does not take into account 198 . In their analysis of Posner spin dynamics they take a number of other factors into account such as dipolar and scalar couplings within Posner molecules as well as the Zeeman interaction of the phosphorus spins with the geomagnetic field 198 .…”
Section: Entangled Posner Moleculesmentioning
confidence: 99%
“…However, they argue that these extended times are partly due to experimental control of the coherent spin dynamics, a condition that Fisher does not take into account 198 . In their analysis of Posner spin dynamics they take a number of other factors into account such as dipolar and scalar couplings within Posner molecules as well as the Zeeman interaction of the phosphorus spins with the geomagnetic field 198 . With these as the dominant relaxation pathway they arrive at a relaxation time of 37 minutes, as opposed to Fisher's shortest estimation of approximately a day.…”
Section: Entangled Posner Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7] More recently, it has been proposed that the 31 P nuclear spins within PMs can exhibit long-lived entanglement, and that this could play an important role in nervous excitation via synaptic Ca 2+ ion release. [8][9][10] These and other studies 11 have subsequently explored PMs as potential "neural qubits", drawing upon the fact that nuclear spin coherence times associated with these systems have been found to be exceptionally large per theoretical estimates. Such studies have suggested or assumed that the prototypical structure for the PM is one with an S 6 molecular point group symmetry, at least on average.…”
Section: Introductionmentioning
confidence: 99%
“…12 Certain molecular symmetries can render the six 31 P nuclei magnetically equivalent (e.g., S 6 ), resulting in a small number of unique scalar (J) couplings (e.g., three unique coupling constants for S 6 ). 11 Understandably, other molecular symmetries could treat groups of 31 P nuclei as distinct, thus, resulting in a larger number of pertinent scalar couplings. 13 As the ability of the system to sustain long-lived spin coherences is starkly related to the asymmetry in the coupling network, [14][15][16][17][18] the spin physics of PMs is inherently linked to the molecule's point group symmetries.…”
Section: Introductionmentioning
confidence: 99%